Gravitational-Wave Detection Using Pulsars: Status of the Parkes Pulsar Timing Array Project - Hobbs, G.; Bailes, M.; Bhat, N.; Burke-Spolaor, S.; Champion, D.; Coles, W.; Hotan, Aidan (CSIRO, 2009)
The first direct detection of gravitational waves may be made through observations of pulsars. The principal aim of pulsar timing-array projects being carried out worldwide is to detect ultra-low frequency gravitational waves (f ~10-9-10-8 Hz). Such waves are expected to be caused by coalescing supermassive binary black holes in the cores of merged galaxies. It is also possible that a detectable signal could have been produced in the inflationary era or by cosmic strings. In this paper, we review the current status of the Parkes Pulsar Timing Array project (the only such project in the Southern hemisphere) and compare the pulsar timing technique with other forms of gravitational-wave detection such as ground- and space-based interferometer systems